2014
DOI: 10.1111/j.1532-950x.2014.12110.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Rostral Mandibulectomy for Treatment of Ameloblastoma in a Horse

Abstract: Extensive rostral mandibulectomy (up to the caudal edge of the mandibular symphysis) can apparently be performed in a horse without internal or external stabilization, and yield a cosmetic and functional outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 18 publications
(30 reference statements)
1
24
0
Order By: Relevance
“…At follow up 18 months later, there was no evidence of recurrence. 29 The various subsets of ameloblastomas may explain the very variable CT characteristics we found. These findings were consistent with a similar case series, conducted by Amory et al 12 looking at the CT characteristics of odontogenic tumors in dogs in which variable and inconsistent imaging results of ameloblastomas were found.…”
Section: Discussionmentioning
confidence: 90%
“…At follow up 18 months later, there was no evidence of recurrence. 29 The various subsets of ameloblastomas may explain the very variable CT characteristics we found. These findings were consistent with a similar case series, conducted by Amory et al 12 looking at the CT characteristics of odontogenic tumors in dogs in which variable and inconsistent imaging results of ameloblastomas were found.…”
Section: Discussionmentioning
confidence: 90%
“…It was not possible to exclude invasion of the cancellous bone of the maxilla, which would have indicated a higher likelihood of recurrence if surgical excision had been attempted. Rostral mandibulectomy and hemi‐mandibulectomy have been described for treatment of a mandibular ameloblastomas in adult horses . Surgical excision of the maxillary tumour in this case would have necessitated excision of portions of the right maxilla, the nasal septum and the permanent cheek teeth dental buds, causing significant disfiguration of the nose and dental arcades.…”
Section: Discussionmentioning
confidence: 96%
“…In this case complete excision resulted in loss of the symphysis and instability of the mandibles. In horses, resection of the mandible caudal to the symphysis may not require stabilization . Mendez‐Angulo et al reported performing a rostral mandibulectomy in an 19‐year‐old horse with an invasive ameloblastoma.…”
Section: Discussionmentioning
confidence: 99%